Possibility of studying geophysical oscillatory processes and perturbations according to the astronomical hours of Fedchenko - Slivinsky, A. P.; Kalyuzhny, N. A.; Bushuyev, F. I. (Geofizicheskiy Zhurnal, 2011)
On an equipment and software complex of the research institute NAO the long-period oscillations determined by dynamics of the Earth's inner core and of the tidal forces have been confirmed upon the analysis of temporal and spectral sequences of the reading deviations of the astronomical pendulum clock of Fedchenko (ACF). A processing method of the ACF readings has been developed. A model of the ACF reading deviations is proposed to simulate the physical processes determining the dynamics of perturbations. Short-period oscillations associated with spherical and toroidal free oscillations of the Earth have been detected after the strong Sichuan earthquake of 12.05.2008. Seismic waves from earthquakes are detected by abnormally large sudden departures of the ACF readings. A preliminary calibration of the ACF readings by the superconducting gravimeters readings is shown. Characteristics of micro seismic events caused by wind loads were reaffirmed. Anomalies interpreted as a "precursor" has been observed a few minutes before the arrival of seismic wave from certain earthquakes. These anomalies are manifested in a significant reduction of the background dispersion of the ACF readings.